POTENSI BAKTERI LAUT UNTUK BIOREMEDIASI - Nur Fitriah Afianti (Pusat Penelitian Oseanografi LIPI, 2018)
POTENCY OF MARINE BACTERIA FOR BIOREMEDIATION. Marine bacteria have a high abundance on variation as well as the qenes, so it can be used in variousaspects, including the prevention of marine pollution through bioremediation. High genetic variations provide a source of marine bacteria which has decompose-various substances capability. Various studies have been conducted to determine the potential of marine bacteria in degrading pollutants, including degradation of hydrocarbons, PAH, plastic, PCB and removal of heavy metal. Recombination through the insertion of the marine bacteria’s gene coding enzyme has been also performed on indigenous actinomycetes on soil.